Gender mainstreaming in the education sector: Impacts on social transformation - Yakubu , Funom Rapha (Corpus Intellectual, 2023)
Socio-cultural norms, especially in developing nations, havean undeniable effect on all aspects of human lives and development, cutting across the social, economic, political, and personal development of individuals and groups of people. The consequences of which have driven unfair representation, participation, and benefitting of programs, policies, and projects aimed at improving the standard of living of citizens. The benefits of education to the growth and development of individuals and the state have been widely addressed in the literature. From helping people with the necessary skills required to gain significant competitive advantage in the growing markets, to increasing the quality manpower needed to build the infrastructures of a society, it cannot be denied that it is an essential human right of every individual. Despite this, not all individuals are given equal rights to pursue education either formal or informal based on their gender. This paper, therefore, engaged in an extensive review of literature in understanding the global fight for equality in education – the Sustainable Development Goal 4, gender mainstreaming as a useful tool to aiding this fight, Nigeria’s efforts in aligning to the global agenda through gender mainstreaming, socio-cultural factors impeding these efforts as well as recommendations for a better gender-sensitive approach to mainstreaming gender in education. Furthermore, this paper employed mainly secondary sources of data collection to arrive at its findings and conclusions. In its findings, it noted that gender inequality saddled by cultural connotations of what it is to be a woman or a girl child is the primary reason for the unequal participation, representation, and benefiting of girls in education. It also established that despite Nigeria’s efforts to increase the participation of girls in schools, until it addresses the root causes of this disparity in number, using a bottom-up approach, nothing much will be achieved. It, therefore, recommends having a strategic plan that looks at the roles of everyone in society from the government to those at the grassroots level in advocating for proper gender mainstreaming mechanisms in education.